Implementing models of care for musculoskeletal conditions in health systems to support value-based care. Issue 5 (October 2020) - Speerin, Robyn; Needs, Christopher; Chua, Jason; Woodhouse, Linda J.; Nordin, Margareta; McGlasson, Rhona; Briggs, Andrew M.
Abstract: Models of Care (MoCs), and their local Models of Service Delivery, for people with musculoskeletal conditions are becoming an acceptable way of supporting effective implementation of value-based care. MoCs can support the quadruple aim of value-based care through providing people with musculoskeletal disease improved access to health services, better health outcomes and satisfactory experience of their healthcare; ensure the health professionals involved are experiencing satisfaction in delivering such care and health system resources are better utilised. Implementation of MoCs is relevant at the levels of clinical practice (micro), service delivery organisations (meso) and health system (macro) levels. The development, implementation and evaluation of MoCs has evolved over the last decade to more purposively engage people with lived experience of their condition, to operationalise the Chronic Care Model and to employ innovative solutions. This paper explores how MoCs have evolved and are supporting the delivery of value-based care in health systems.